Study of the Lange Glacier and its impact due to temperature increase in Admiralty Bay, King George Island, Antarctica - Mojica-Moncada, Diego F.; Cardenas Mansilla, Carlos Alberto; Mojica-Moncada, Jhon F.; Brondi, Fabian; Barragán-Barrera, Dalia C.; Marangunic, Cedomir; Holland, David; Franco Herrera, Andrés; Casassa, Gino (My University, 2021)
ABSTRACT In the western Antarctic Peninsula one of the areas the highest warming in the southern hemisphere has been identified. To characterize this tendency, we selected the Lange Glacier (LG) on King George Island, to evaluate: 1) LG surface temperature and dynamics using stakes with temperature data loggers; 2) LG submerged thickness and sea parameters through bathymetry (BT) and 29 CTD stations in front of LG; 3) glacier front (GF) using BT and a Digital Elevation Model (DEM); 4) change in GF position using DEM and historical data of GF width; 5) Calving flux (QC). Our findings showed 85 % of temperatures were above the 0 °C melting point (mean = 5.0 ± 5.2 °C). The stakes had an average ice loss of 9.3 ± 1.3 cm. The LG mean dynamics was 8.8 ± 1.5 m (0.40 ± 0.70 m/day), corroborated by Sentinel-1 satellite images (Offset Tracking = 0.43 ± 0.01 m/day). An intrusion of external waters warmer in the LG bay was identified, which destabilizes the water column due to convection processes. Our findings together indicated a continuous glacial melt that increases its dynamics due to the increase in temperature, with a contribution of fresh water to the Admiralty Bay. Based on historical results and this study, the LG retracement was estimated in 2,492 m between 1956 and 2019.
Keywords: lange glacier; melting; climate change; calving flux; antarctica